Adesão à farmacoterapia em pacientes com hipertensão arterial : overview de revisões sistemáticas - Santos, Aline de Jesus (2017)
INTRODUCTION: Increasing morbidity and mortality rates caused by arterial hypertension and health care expenditures have been a serious public health problem. Adherence to treatment is critical to overcome this problem. There are a large number of studies on the subject, but rarely all relevant points and potential interventions for the situation are addressed in a single systematic review, leaving a gap for decisions in clinical practice. So this justifies the importance of elaborating an overview able to compile information from relevant reviews on adherence to pharmacotherapy in hypertensive patients. METHODOLOGY: The research design is in accordance with the definitions reported in the PRISMA statement. The sample is composed of systematic reviews that address the adherence of hypertensive patients to the treatment. The search for the studies was carried out in the databases COCHRANE, LILACS, PubMed / Medline, SCOPUS, Web of Science and the evaluation of the methodological quality of the studies was evaluated through the AMSTAR instrument. RESULTS: A total of 1,094 records were identified on the subject in the respective databases. At the end of the selection process, 17 systematic reviews fulfilled the inclusion criteria in this study. The quality of the systematic reviews ranged from low (3 points) to high (10 points), according to the AMSTAR quality assessment instrument. The number of studies included in the systematic reviews ranged from 6 to 101, with an average of 36 studies per systematic review, providing a total of 612 primary studies included in the overview. The most used methodologies to measure adherence were self-report, pill count and electronic medication monitoring (MEMS). Interventions were more effective in women, elderly and moderate in patients with high socioeconomic status. And increased adherence to antihypertensive drugs and blood pressure control were more effective in multifactorial or complex interventions, including combinations of different strategies, which are performed over several days. CONCLUSIONS: Several sources of heterogeneity were identified in the systematic reviews and meta-analysis on the adherence of hypertensive patients to treatment, thus demonstrating that there is a need to create specific quality criteria for studies that evaluated adherence. In addition, no method described in the literature can be considered the gold standard for assessing adherence to treatment in hypertensive patients and there is no single intervention that can be considered as the best option to improve adherence to the treatment of hypertensive patients. Due to the complexity of the adhesion process, it is necessary for the health professional to know the individual characteristics of the patients and to formulate specific interventions according to the needs of each individual.